2010
DOI: 10.1007/s00264-010-1058-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of post-coccygectomy infection in a series of 136 coccygectomies

Abstract: Postoperative infection is a regular complication in coccygectomy. The authors propose the use of a topical skin adhesive on the postoperative wound as a contribution to the prevention of this complication. It was used on the first 56 patients in this study. The rate of infection was 3.6% compared with the 14% rate of infection in a previous study. The 80 following patients had, in addition to the skin adhesive, two prophylactic antibiotics for 48 hours (cefamandole and ornidazole), a preoperative rectal enema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
2
23
1
Order By: Relevance
“…A recent systematic review of 671 coccygectomy patients, reported a complication rate following coccygectomy of 10.9% 34 Most were wound problems that resolved with antibiotics and local treatment. 6,9,10,21,35,36 This study is a prospective analysis of a large series of patients treated by a single surgeon with extensive experience with the procedure. It reinforces the argument that patients with chronic coccydynia can benefit from surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of 671 coccygectomy patients, reported a complication rate following coccygectomy of 10.9% 34 Most were wound problems that resolved with antibiotics and local treatment. 6,9,10,21,35,36 This study is a prospective analysis of a large series of patients treated by a single surgeon with extensive experience with the procedure. It reinforces the argument that patients with chronic coccydynia can benefit from surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the literature Kleimeyer and colleagues report postoperative dehiscence and infection rates ranging from 0% to 30% 3) . Infection is most commonly with S. aureus 7) , however recent authors have reported using preoperative rectal enemas and broadening antibiotics to cover gram negative microbes 8) . In our patients we use cefazolin intravenously with 1 gram applied directly into the wound at the end of the case.…”
Section: Discussionmentioning
confidence: 99%
“…2,20,34 Opponents think its proximity to the rectum may be a cause for increased infection rates. 36 Patients are positioned lateral or supine after the surgery to avoid pressure to the surgical wound. 8,9 For closure, the periosteum, fascia, and skin are closed in layers.…”
Section: Coccygectomymentioning
confidence: 99%
“…36 Perioperative prophylactic broad-spectrum antibiotics should be administered during a period of 48 hours. 36 Perioperative prophylactic broad-spectrum antibiotics should be administered during a period of 48 hours.…”
Section: Adverse Effectsmentioning
confidence: 99%